Sejarah Perjuangan Sultan Mahmud Badaruddin II - Risman, Delfia Chintika; Sukardi, Sukardi; Zamhari, Ahmad (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Sultanate of Palembang Darussalam is a historical Islamic kingdom located in the area now known as the city of Palembang, South Sumatra, Indonesia. The sultanate was officially proclaimed as an Islamic kingdom by its leader, Sri Susuhunan Abdurrahman, who later established Islamic identity as the main basis of his rule. Sultan Mahmud Badaruddin II is the sixth Sultan of Palembang Darussalam who is the son of Sultan Mahmud Badaruddin II was born in Palembang in 1767. When he was appointed as Sultan, he was 36 years old. The goal is to find out how the Sultan Mahmud Badaruddin II is going. The method used in this study is qualitative descriptive. The result of this research is that Sultan Mahmud Badaruddin II led Palembang in a challenging period and tried to defend its territorial sovereignty from foreign intervention, both Dutch and British. Sultan Mahmud Badaruddin II’s fierce resistance culminated in a major battle against the Dutch in 1819, although he was eventually captured and exiled to Ternate in 1821.